Energy consumption in the swimming pool building using heat recovery from grey water - Żabnieńska-Góra, Alina; Liebersbach, Joanna; Polarczyk, Iwona (Instal, 2025)
Grey water is a very good source of waste heat. This heat can be used to pre-heat domestic or process water, which has a significant impact on the final energy consumption of the building. Swimming pool facilities are among the buildings with high water and energy demand. Considering the number of swimming pool facilities in Poland, this article presents a theoretical analysis of the possibility of reducing energy consumption in an indoor swimming pool building through the application of energy-saving technologies based on the use of heat recovery from grey wastewater from showers.